Managing Public Facilities through Partnership ContractsA comparative Study - صادق, علي (Thi Qar Arts Journal, 2025)
This research examines public-private partnership (PPP) contracts as a modern mechanism for managing public facilities, with a particular focus on their conceptual and legal framework through a comparative study of selected Arab legislations. The growing role of the state and its increasing financial obligations have limited its ability to meet the rising demands for infrastructure and public services. This situation has highlighted the need for alternative approaches to financing and management. In this context, partnership with the private sector has emerged as a strategic option to achieve sustainable development without resorting to full privatization and its associated negative consequences. The study defines partnership contracts from legislative and juristic perspectives, emphasizing the differences between the Iraqi, Egyptian, and Lebanese experiences. It also addresses the general principles governing these contracts, such as competition, transparency, and equal opportunity, in addition to the exceptional powers granted to public authorities regarding supervision and unilateral modification. The research highlights the key drivers for adopting PPPs, including inefficiency in public sector management, the need for massive investments in infrastructure, the attraction of foreign capital, and the transfer of advanced technology. On the other hand, it identifies major risks associated with PPPs, such as delays in implementation, financial instability, operational risks, and market monopolies. Furthermore, the research outlines the essential stages of PPP contracts—from project proposal and bid evaluation to the establishment of a project company and monitoring of implementation. A comparative analysis of the legal frameworks in Egypt, Lebanon, and Jordan is provided, while pointing out the lack of a comprehensive legislative framework in Iraq. The study concludes that PPPs can serve as an effective alternative for supporting sustainable development, provided that a clear legal framework is established to define their nature as administrative contracts and to balance the interests of both the state and the private sector. Finally, the authors recommend the adoption of specific PPP legislation in Iraq to create a more conducive legal and investment environment that safeguards public funds and ensures the achievement of economic and social objectives.